EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION PADA MATERI POKOK PERSAMAAN DAN PERTIDAKSAMAAN LINIER SATU VARIABEL DITINJAU DARI ADVERSITY QUOTIENT SISWA KELAS VII SMP NEGERI SE-K - Wijayanti, Septiana; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research aimed to find out: (1) which one gives better in mathematics learning achievement, learning models of Teams Games Tournament (TGT) with Realistic Mathematics Education (RME) approach, Teams Games Tournament (TGT) or conventional, (2) which one have better in mathematics learning achievement, students having climbers, campers or quitters of Adversity Quotient,Â  (3) in each learning model, the level of Adversity Quotient which one hve better mathematics learning achievement, students having climbers, campers or quitters of Adversity Quotient, (4) in each studentâs level of Adversity Quotient which one gives better in mathematics learning achievement, learning models of TGT with RME approach, TGT or conventional. This research was a quasi-experimental research with 3 x 3 factorial design. The population of research was all students of Junior High School (SMP) in Grobogan. The samples were chosen by using stratified cluster random sampling. The instruments that were used to collect the data were the documentation of mathematics achievement, questionnaire of Adversity Quotient and test of mathematics achievement. The technique of analyzing the data was two-ways ANOVA with unbalanced cells. The result of research showed as follows: (1) learning model TGT with RME approach provided better learning achievement than TGT and conventional, learning TGT provided better learning achievement than conventional, (2) the students having climbers, campers, and quitters had equally mathematics learning achievement, (3) in each learning model, the students having climbers, campers, and quitters had equally mathematics learning achievement, (4) in each Adversity Quotient, learning model TGT with RME approach provided better learning achievement than TGT and conventional, learning TGT provided better learning achievement than conventional.Keywords: Teams Games Tournament (TGT), Realistic Mathematics Education (RME) approach, and Adversity Quotient (AQ)